Advancing human genetics research and drug discovery through exome sequencing of the UK Biobank - Szustakowski, Joseph D.; Balasubramanian, Suganthi; Kvikstad, Erika; Khalid, Shareef; Bronson, Paola G.; Sasson, Ariella; Wong, Emily; Liu, Daren; Wade Davis, J.; Haefliger, Carolina; Katrina Loomis, A.; Mikkilineni, Rajesh; et al. (Nature genetics, 2021)
The UK Biobank Exome Sequencing Consortium (UKB-ESC) is a private–public partnership between the UK Biobank (UKB) and eight biopharmaceutical companies that will complete the sequencing of exomes for all ~500,000 UKB participants. Here, we describe the early results from ~200,000 UKB participants and the features of this project that enabled its success. The biopharmaceutical industry has increasingly used human genetics to improve success in drug discovery. Recognizing the need for large-scale human genetics data, as well as the unique value of the data access and contribution terms of the UKB, the UKB-ESC was formed. As a result, exome data from 200,643 UKB enrollees are now available. These data include ~10 million exonic variants—a rich resource of rare coding variation that is particularly valuable for drug discovery. The UKB-ESC precompetitive collaboration has further strengthened academic and industry ties and has provided teams with an opportunity to interact with and learn from the wider research community. The UK Biobank Exome Sequencing Consortium aims to sequence all the exomes of approximately 500,000 UK Biobank participants. This Perspective describes the results from approximately 200,000 exomes and discusses the lessons learned from this UK Biobank–biopharmaceutical company collaboration.